Correlation Between Duration of Diabetes Mellitus and Visual Acuity Among Patients with Diabetes Mellitus - Eny Masruroh; Niken Mei Risky (Health Gate, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder that can lead to various complications, including diabetic retinopathy, which may result in decreased visual acuity. The duration of diabetes is considered an important factor influencing the development of such complications. Objective: This study aims to analyze the correlation between duration of diabetes mellitus and visual acuity among patients with diabetes mellitus. Methods: his study employed a correlational analytic design with a cross-sectional approach. The study was conducted from February to March 2024 in Ngunut Village, Tulungagung Regency. A total of 30 respondents were selected using purposive sampling. The independent variable was the duration of diabetes mellitus, while the dependent variable was visual acuity measured using a Snellen chart. Data were analyzed using the Chi-square test with a significance level of 0.05. Results: The majority of respondents had diabetes mellitus for more than 5 years (56.7%, n=17), and most experienced decreased visual acuity (60%, n=18). The Chi-square test showed a p-value of 0.001 (p < 0.05), indicating a significant association between the duration of diabetes mellitus and visual acuity. Conclusion: here is a significant correlation between the duration of diabetes mellitus and visual acuity. Patients with longer disease duration are more likely to experience visual impairment. Early detection and proper management are essential to prevent complications.